9-2x-7=6x+4-2x

Simple and best practice solution for 9-2x-7=6x+4-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-2x-7=6x+4-2x equation:


Simplifying
9 + -2x + -7 = 6x + 4 + -2x

Reorder the terms:
9 + -7 + -2x = 6x + 4 + -2x

Combine like terms: 9 + -7 = 2
2 + -2x = 6x + 4 + -2x

Reorder the terms:
2 + -2x = 4 + 6x + -2x

Combine like terms: 6x + -2x = 4x
2 + -2x = 4 + 4x

Solving
2 + -2x = 4 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
2 + -2x + -4x = 4 + 4x + -4x

Combine like terms: -2x + -4x = -6x
2 + -6x = 4 + 4x + -4x

Combine like terms: 4x + -4x = 0
2 + -6x = 4 + 0
2 + -6x = 4

Add '-2' to each side of the equation.
2 + -2 + -6x = 4 + -2

Combine like terms: 2 + -2 = 0
0 + -6x = 4 + -2
-6x = 4 + -2

Combine like terms: 4 + -2 = 2
-6x = 2

Divide each side by '-6'.
x = -0.3333333333

Simplifying
x = -0.3333333333

See similar equations:

| -75-k=195 | | 2(3k-1)/5+4=3k | | x+54=4x | | (6+2x)(3+3x)=8 | | 111118n^2+60n+50=0 | | 2(3k-1)/5+4=3k(5) | | a+10=67 | | (2x^2+7x)-(x^2-6x-2)= | | 5x^2+20x+31=0 | | p+50=149 | | 2x-56=14 | | 10p(3s)= | | 9(3n-4)=(7n+4)1 | | 25y^2-144=0 | | 22=-4p-10 | | 10p(3s+10p)= | | n-14=92 | | 4+6p-6p=p-2 | | m+20=30 | | x^2+6x+5=9 | | 3y+19=47+2y | | 3/7H=-18 | | 5(6x+2)+6=30x+16 | | 5y=12y+20 | | 2+7(10+15k)= | | .8x-2.9=.3 | | -x^2=-4x | | 3x-5x=8x | | x-(8-3x)=2(3x+5) | | 3m^2+30m+75= | | 8-(2n-6)=2-3n | | -8y^2=10y |

Equations solver categories